Approaches to economic evaluations of stroke rehabilitation. Issue 1 (22nd March 2013) - Craig, Louise E; Wu, Olivia; Bernhardt, Julie; Langhorne, Peter
<x xml:space="preserve">Abstract</x> Many stroke rehabilitation services and interventions are complex in that they involve a number of components, interactions, and outcomes. Much of the onus of stroke care lies with rehabilitation services and because stroke rehabilitation is highly resource intensive, it is important for policy makers to consider the potential trade‐offs between all relevant costs and benefits. The primary aim of this systematic review was to assess the methods used to conduct economic evaluations of stroke rehabilitation. Studies that compared two or more alternative stroke rehabilitation interventions or services with the costs and outcomes being examined for each alternative were included. EMBASE, MEDLINE In‐Process, and National Health Service's Economic Evaluation Database were searched using search strategies. The methodological quality of the included studies was appraised using a checklist for the conduct and reporting of economic evaluations. Twenty‐one studies met the selection criteria. The economic evaluations in the majority of these studies were inadequate based on their ability to identify, measure, and value all resources and benefits pertinent to the complexity of stroke rehabilitation. This study highlights that complex interventions such as stroke rehabilitation have widespread effects, which may not be represented by the changes on a single outcome. This study recommends the adoption of a wider cost and benefit perspective in the economic evaluations of complex interventions. It supports a move away from conventional economic evaluation and decision making, based purely on cost‐effectiveness, toward multicriteria decision analysis frameworks for complex interventions, where a broader range of criteria may be assessed by policy makers.